MANAJEMEN RISIKO PEMBIAYAAN MUSYARAKAH MUTANAQISAH DI BANK MUAMALAT INDONESIA KC MAS MANSYUR SURABAYA - Gea Papurane Langi; Imron Mawardi (Jurnal Ekonomi Syariah Teori dan Terapan, 2019)
This research is done to see any risks that happened in Islamic bank, which can damage the bank. While it aims to find out the strategy used by Bank Muamalat Indonesia (BMI) to reduce the risk faced and often happened in the field. The research method uses a qualitative approach with a case study method. Data collecting was done by relating proposed questions and the conclusion made from the result of the interview with Branch Manager (BM), Relation Manager, and Remedial BMI of Branch Office of Mas Mansyur. The result of this research showed that BMI of Mas Mansyur Branch Office had done the process of risk management by identifying risk in the manner of finding out the existing risks which are financing risk; market risk; and ownership risk, measuring and monitoring the risks in the manner of doing measurement to find out and see any reason that causes those risks exist, and controlling and managing the existing risks in Musyarakah Mutanaqisah (MMQ) financing in the manner of ways that have already determined by BMI of Mas Mansyur Branch Office. The last is by monitoring the risks in MMQ financing at BMI of Mas Mansyur Branch Office.Keywords: Risk Management, Risk, Financing, Musyarakah Mutanaqisah, Bank Muamalat IndonesiaREFERENCES Dsnmui.or.id diakses pada 11  september2017 pukul 21.41Hosen,   M    Nadratuzzaman   Hosen.   13November 2017. www.ekonomisyariah.orgKarim A, Adiwarman. 2014. Bank Islam: analisis fiqih dan keuangan. Jakarta. PT. Raja Grafindo Persada.Nafik HR, Muhammad, 2009. Bursa Efek dan Investasi Syariah. jakarta: PT. Serambi Ilmu SemestaNaf’an,2014.  Pembiayaan  Musyarakah dan Mudharabahi. Yogyakarta: Graha IlmuStandar Produk Perbankan Syariah Musyarakah dan Musyarakah Mutanaqisah, 2016.Sugiyono, Prof. Dr. 2012. Metode Penelitian Kuantitatif, kualitatif, dan R&D. Bandung: Alfabeta.Wahyudi, Imam, et al. 2013. Manajemen Risiko Bank Islam. Jakarta: Salemba Empat.Yin, Robert K. 2009. Studi kasus: desain& Metode. Jakarta: Prenada media.